Foreign ownership and sustainability performance in Indonesia - Hesty Erviani Zulaecha; Murtanto Murtanto (International Journal of Financial, Accounting, and Management, 2019)
Purpose: This research is designed to find empirical evidence on the influence of Foreign Ownership as moderating to enterprise risk management, business strategy, and firm age on sustainability performance. Research Methodology: This research was tested through random samples of 11 manufacturing companies period 2014-2017. Regression analysis was adopted to test the hypotheses significant influence to sustainability performance. But, the firm age doesn’t have influence on sustainability performance. Limitation: The use of secondary data and content analysis methods that cause limitations in conclusions and are subjective. Implication: This research shows that the harmonious relationship between strategic management related to enterprise risk management, business strategy, and the role of foreign ownership to achieve high sustainability performance. Keywords: Sustainability performance, Business strategy, Foreign owner, Enterprise risk management, Firm age How to Cite: Zulaecha, Hesty & Murtanto. (2019). Foreign ownership and sustainability performance in Indonesia. International Journal of Financial, Accounting, and Management, 1(1), 1-15.